Existence of solutions for elliptic equations having natural growth terms in Orlicz spaces - A. Elmahi; D. Meskine (Abstract and Applied Analysis)
Existence result for strongly nonlinear elliptic equation with a natural growth condition on the nonlinearity is proved.